Sensory feedback for gait in transtibial amputees: a narrative review of technologies and clinical outcomes - Suliman Hussain, Rita; Abd Razak, Nasrul Anuar; Alfatafta, Mahmoud; Chow Khuen, Chan; Al Qaroot, Bashar; Ramousse, Timothé (Frontiers in Bioengineering and Biotechnology, 2026)
The loss of somatosensory feedback in transtibial amputees contributes to gait asymmetry, increased metabolic cost, higher fall risk, and dependence on visual cues. Sensory neuroprostheses, both invasive and non-invasive, provide methods to restore aspects of this feedback and enhance functional mobility. This review combines recent findings from invasive procedures, such as intraneural electrodes, spinal cord stimulation, and agonist–antagonist myoneural constructs, with non-invasive electrotactile, mechanotactile, and vibrotactile techniques. Invasive systems offer high-quality somatotopic mapping that improves embodiment and reduces phantom limb pain but are limited by surgical risks, long-term stability issues, and scalability concerns. Non-invasive systems, especially those utilizing vibrotactile feedback, have demonstrated measurable benefits, including a 41% increase in walking speed, fewer stumbles, improved symmetry indices from approximately 60% to roughly 75%, and a 70% reduction in phantom limb pain in small clinical trials. However, most studies are limited by small sample sizes, short intervention durations, and laboratory-based testing, with inconsistent reporting of cognitive load, training doses, and real-world applicability. The analysis here highlights vibrotactile systems as the most practical near-term option for clinical use, while invasive approaches remain valuable for high-performance tasks requiring precise feedback. Future research should focus on larger, longer trials, standardized outcome reporting, and seamless integration of sensors and actuators into prosthetic sockets. Overcoming these challenges is key to developing scalable, next-generation sensory feedback systems capable of restoring natural and confident gait in transtibial amputees.